The Relationship between Brand Ambassador Song Joong Ki with Scarlett Whitening Brand Image - Fajri, Aminah Devina; Putri, K. Y.S.; Safitri, Dini (Universitas Ahmad Dahlan, 2022)
With the development of technology and information, the competition between companies is getting tougher. Using a brand ambassador is undoubtedly one of the marketing strategies that can communicate the brand and improve the brand image. Of course, every company wants its products to have a good impression and be accepted by various circles of society. The purpose of the study was to determine the relationship between the Scarlett Whitening brand ambassador, Song Joong Ki, and the brand image of the Scarlett Whitening product. This research uses descriptive quantitative analysis. The sampling technique used in this research is purposive sampling. The data collection used in this research is using a questionnaire. The results of this study obtained the correlation coefficient of the X variable, namely the brand ambassador, with the Y variable, namely the brand image, 0.997. This value proves that Song Joong Ki's brand ambassador has a strong relationship with the brand image of Scarlett Whitening products.